Corrosion of Reinforced Concrete Structures Submerged by the 2004 Tsunami in West Aceh, Indonesia. (7th August 2018) - Susanto, Herdi; Huzni, Syifaul; Fonna, Syarizal
Abstract : The earthquake and tsunami of 26 December 2004 caused the infrastructure in Aceh's West Coast region to be submerged by seawater and to require the rehabilitation and reconstruction. The infrastructure that was submerged in the tsunami might experience a decrease in strength due to corrosion attack and would unexpectedly collapse if an earthquake occurs even on a small scale. This study was conducted to examine the corrosion risk level of the infrastructures in Aceh's West Coast region, Indonesia, which submerged by the 2004 tsunami. Three locations were chosen for the study, i.e., Suak Ribee, Ujong Kalak, and Padang Seurahet. The assessments were carried out in 2014 and 2015. Three to four columns in each of the buildings were selected for the assessment. The half-cell potential technique method which refers to ASTM C876 was used to obtain and analyze the assessment data. The results of the assessment show that the electrical potentials on the surface of concrete for the buildings which submerged by the tsunami were range between -100 and -450 mV (vs. Cu/CuSO4 ) and categorized into low to high corrosion risk level. Meanwhile, the electrical potentials for new buildings range between (-100) and (-350) mV which indicated low to medium corrosion risk. Hence, the corrosion actively occurred in the areas having medium to high corrosion risk. Also, it was found that the corrosion risk level for the building tends to increase by increasing time. Therefore, the prevention and/or rehabilitation is necessary for stopping the corrosion, and so the premature failure of the building might be avoided.